Impact of Claim Settlement on Sales of Life Insurance Policies – A Case Study of LIC of India (International Journal of Scientific Research and Management (IJSRM), 2017)
Claim settlement is one of the most important parts of the life insurance services. Person who is holding or planning for the life insurance will always want to have prompt claim settlement. For any insurance company sales of insurance policies is the biggest source of revenue and if claim are not properly settled then it will affect its sales. The study is based on the secondary data collected from IRDA annual report and it shows that LIC of India continue to grow due to its prompt claim settlement, highest insurance premium collections and highest number of policies sold.